The Importance of Peers for Compliance with Norms of Fair Sharing - Simon Gächter; Leonie Gerhards; Daniele Nosenzo (Institute for the Study of Labor (IZA), 2015)
A burgeoning literature in economics has started examining the role of social norms in explaining economic behavior. Surprisingly, the vast majority of this literature has studied social norms in asocial decision settings, where individuals are observed to act in isolation from each other. In this paper we use a large-scale dictator game experiment (N = 850) to show that the presence of "peers" in the decision setting faced by an individual can have a profound influence on the individual's perception of the decision situation and its underlying norms of sharing, as elicited in an incentive compatible way. However, we find limited evidence that this influence of peers in normative considerations translates into a corresponding effect in actual behavior. Partly, this is due to substantial heterogeneity in the extent to which dictators in our sample are willing to comply with norms of fair sharing.
Keywords: A13; C92; D03; 330; social norms; norm compliance; peer effects; fair sharing; dictator game; framing; experiments